RESPONSE OF TWO CABBAGE HYBRID TO SPRAYING WITH VEGEAMINO AND ALGATON 20 AND COVERED WITH AGRAL UNDER SUSTAINABLE AGRICULTURE SYSTEM - & et al., Sadik (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Sustainable agriculture was adopted in field experiment in horticulture vegetable field during fall season 2013-2014, to study the effect of spraying nutrients and agral on cabbage hybrid yield, Split –split plot experimental as RCBD design with three replicates at 10 plants for each treatment was adopted, Tropicana and Redball (A and B) transplants (main plot) at 45 day age tranplanted to open field at 25/9/2013 plants, Vegeamino (T2) and Algaton 20 (T3) spraying with 1ml L-1 three times for two week intervals for each of them while control plants (T1) spraying with distilled water (sub plot), plants covered (sub-sub plot) with agral C1 control plant (C0) (without agral), Results showed that was B hybrid, BT1, BC0 and T1C0 increased cabbage head leaves, BT1C0 increased head leaves at 43.33 leaf head-1, Leaf area was higher in A hybrid than B hybrid, B hybrid increased total plant leaves than A hybrid, also increased in BT1, BC0 and BT1C0 as compared with lowest number in AT1, AC1 and AT1 treatments, A hybrid increased cabbage head weight and total yield, higher head weight and total yield was 1375 gm and 10.74ton ha-1 in AT3 treatment as compared with 535 gm and 4.18 ton ha-1 respectively, AC0 increased head weight and total yield at 1350gm and 10.55ton ha-1 respectively, higher head weight and total yield was 1567gm and 12.24ton ha-1 in AT3C0 respectively, it was concluded from these results that spraying Tropicana hybrid plants with Algaton 20 with or without agral  enhanced most yield and significantly increased most studying characters.